Cancer risk in patients with Peutz–Jeghers syndrome: A retrospective cohort study of 336 cases. Issue 6 (June 2017) - Chen, Hong-Yu; Jin, Xiao-Wei; Li, Bai-Rong; Zhu, Ming; Li, Jing; Mao, Gao-Ping; Zhang, Ya-Fei; Ning, Shou-Bin
Peutz–Jeghers syndrome is a rare autosomal dominant inherited disorder characterized by mucocutaneous pigmentation and hamartomatous gastrointestinal polyposis. A growing body of evidence has shown that Peutz–Jeghers syndrome could cause an increased risk of various cancers, yet the range of cancer risk estimates was wide among different studies. In this retrospective cohort study, 336 patients with Peutz–Jeghers syndrome in China were enrolled. The clinical characteristics, cancer spectrum, relative cancer risks, and cumulative cancer risks were analyzed. In total, 52 patients were diagnosed of cancer in the follow-up period, at a median age of 41 years (range: 21–67). The relative risk for cancer in Peutz–Jeghers syndrome patients was 63.858 (confidence interval: 47.514–85.823), and the cumulative cancer risk at the age of 60 years was 55%. Colorectal cancer was the most common cancer for Peutz–Jeghers syndrome patients (relative risk: 237.918, confidence interval: 154.417–366.572) and the cumulative cancer risk at the age of 60 years was 28%. There was a statistically significant difference in the cumulative cancer risk between patients with family history and those without family history, as well as between patients living in rural area and those living in urban areas ( p < 0.05), while no significant effects of gender and intussusception history on the cumulative cancer risk was found ( p > 0.05). Hopefully, our study may contribute to the management of this rare disorder and establishment of related surveillance projects, especially in China.